Disparity of Constitutional Court Decisions on The Position of the Corruption Eradication Commission From the Fiqh Siyasah Perspective - Dinda Putri Sabillah Lubis; Afifa Rangkuti (Journal of Law, Politic and Humanities, 2024)
The Constitutional Court Decision No. 36/PUU-XV/2017 states that the Corruption Eradication Commission (KPK) is a state institution in the executive domain. This decision contradicts 3 (three) previous conclusions which stated otherwise that the Corruption Eradication Commission (KPK) is an independent state institution through its decision no. 012-016-019/PUU-IV/2006, No. 5/PUU-IX/2011, Number 49/PUU-XI/2013. This research aims to determine the Constitutional Court Decision Number 36/PUU-XV/2017 regarding the position of the Corruption Eradication Commission as an Independent State Institution in the Indonesian Constitutional Structure. The research method used is juridical-normative legal research with a statutory approach. The data collection technique was carried out by means of library research (library research). This research also reviews the position of the Corruption Eradication Committee (KPK) in the perspective of siyasah fiqh. The concept of the mazalim institution dates back to the Umayyad era. The mazalim institution is a judicial authority that is higher than the al-qada area and the al-hisbah area, namely resolving cases that cannot be resolved by the two judicial institutions. The results of this research explain that Constitutional Court Decision Number 36/PUU-XV/2017 which places the KPK as a state institution whose position and existence is in the executive branch of power has created problems with the KPK's institutional position and relationships. Therefore, the right to inquiry issued by the DPR against the Corruption Eradication Commission is an implementation of the function of legislative oversight of the executive branch (government).